Princess Labelmaker to the rescue! - Angleberger, Tom. (New York : Amulet Books, 2014)
One month before the state standards test is to take place, the Origami Rebel Alliance has found powerful allies in unexpected places in their fight against the FunTime test preparation program, but Principal Rabbski has not yet declared her allegiance.
4.7
3-6
750L
Keywords: Finger puppets -- Juvenile fiction; Origami -- Juvenile fiction; Eccentrics and eccentricities -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Finger puppets -- Fiction; Origami -- Fiction; Eccentrics and eccentricities -- Fiction; Interpersonal relations -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Puppets and puppet plays -- Fiction; Origami -- Fiction; Eccentrics and eccentricities -- Fiction; Interpersonal relations -- Fiction; Middle schools -- Fiction; School stories; Finger puppets -- Fiction; Origami -- Fiction; Eccentrics and eccentricities -- Fiction; Interpersonal relations -- Fiction; Middle schools -- Fiction